Analysis of session sequence of stable peers in P2P networks - ZHANG Yu-xiang1; XIAO Chun-jing1; ZHANG Hong-ke2; XU Tao1 (Tongxin xuebao)
A formal definition of stable peers was presented,a novel method to separate stable peers from all peers and an analysis of the session sequence of stable peers in P2P networks.This study uses the KAD,a P2P file sharing system with several million simultaneous users,as an example and draws some significant conclusions about stable peers: the stable peers is about 0.6% of all peers;the 70% of stable peers possess very long total session time ensured by a large number of sessions,and possess large difference between session time;the 30% of stable peers,whose average session time is 1.8 times of the former,possess long total session time,a small number of sessions and high availability.That these two types of stable peers can play their respective roles in constructing hierarchical P2P networks.